How do you solve 1 - m = 6 - 6m ? Algebra Linear Equations Multi-Step Equations with Like Terms 1 Answer Untitled May 4, 2018 Refer to Explanation Explanation: 1-m = 6-6m 1-m+6m=6-6m+6m 1+5m=6 1+5m-1=6-1 5m=5 m=5/5 m=1 Answer link Related questions How do you solve multi step equations by combining like terms? How do you solve multi step equation w + w + 12 = 40? How do you solve 3p + 4p + 37 = 79? How do you solve for f: f-1+2f+f-3=-4? How do you combine like terms? How do you combine like terms for -7mn-2mn^2-2mn + 8? How do you combine like terms for 3x^2 + 21x + 5x + 10x^2? What is a term? How do you solve 3v+5-7v+18=17? How do you solve for x in 5x + 7x = 72? See all questions in Multi-Step Equations with Like Terms Impact of this question 6652 views around the world You can reuse this answer Creative Commons License